Intravitreous treatment of severe ocular von Hippel–Lindau disease using a combination of the VEGF inhibitor, ranibizumab and PDGF inhibitor, E10030: Results from a phase 1/2 clinical trial. (26th October 2021) - Hwang, Christopher K.; Chew, Emily Y.; Cukras, Catherine A.; Keenan, Tiarnan D. L.; Wong, Wai T.; Linehan, W. Marston; Chittiboina, Prashant; Pacak, Karel; Wiley, Henry E.
Abstract: Background: Treatment options for severe ocular von Hippel–Lindau (VHL) disease are limited. This trial evaluated preliminary safety and potential efficacy of combination intravitreous injection with ranibizumab, a vascular endothelial growth factor (VEGF) inhibitor, and E10030, a PDGF inhibitor, for eyes with VHL disease‐associated retinal hemangioblastoma (RH) not amenable or responsive to thermal laser photocoagulation. Methods: This was a prospective, single‐arm, open‐label phase 1/2 study, comprised of three adults with VHL‐associated RH and vision loss. Intravitreous injections of ranibizumab (0.5 mg) and E10030 (1.5 mg) were given unilaterally every 4 weeks in the study eye through 16 weeks, then every 8 weeks through 48 weeks. Supplementary standard care therapies were allowed without restriction after 40 weeks. The primary outcome was the ocular and systemic adverse effect profile at 52 weeks. Secondary outcomes included changes in best‐corrected visual acuity (BCVA), RH size, exudation, epiretinal proliferation and retinal traction, and need for ablative treatment of RH or ocular surgery at week 52. Results: Three participants each received nine injections prior to week 52 and were followed for 104 weeks. One participant manifested mild episodic ocular hypertension in the study eye. Change in BCVA in the study eye at week 52 for the three participants was −5, −12 and +2 letters. No reduction in RH size was measured at 52 weeks. Variable mild improvements in exudation in two participants at week 16 were not sustained through week 52. Conclusions: Combination intravitreous injection with ranibizumab and E10030 demonstrated a reasonable preliminary safety profile, but limited treatment effect.